Minimally invasive laser treatment combined with intravitreal injection of anti-vascular endothelial growth factor for diabetic macular oedema - Inagaki, Keiji (Sci Rep, 2019)
The purpose of this study was to investigate the effect of the combination of minimally invasive laser treatment to the intravitreal injection of anti-vascular endothelial growth factor (VEGF) for diabetic macular oedema (DME). This study was retrospective longitudinal study of thirty-four eyes of 31 patients with DME. Either once or several times of intravitreal anti-VEGF injection was followed by the single minimally invasive laser within a month. The mean best corrected visual acuity (VA) and the central macular thickness (CMT) were measured before treatment, 1, 3, 6 and 12 months after the first anti-VEGF injection. The mean logMAR VA had improved from 0.52 ± 0.34 at baseline to 0.44 ± 0.32 (p = 0.003), 0.40 ± 0.34 (p = 0.006), 0.43 ± 0.33 (p = 0.063), and 0.41 ± 0.34 (p = 0.009), at 1, 3, 6, and 12 months after treatment, respectively. The mean CMT decreased significantly by 1 month and maintained over 12 months (491.1 ± 133.9 µm at baseline, 396.6 ± 116.8 µm (p = 0.001), 385.2 ± 156.2 µm (p = 0.002), 336.5 ± 86.3 µm (p = 0.000), and 354.8 ± 120.4 µm (p = 0.000) at 1, 3, 6, and 12 months, respectively). The average number of the anti-VEGF injection in 1 year was 3.6 ± 2.1 in all patients. The combined intravitreal anti-VEGF and minimally invasive laser therapy improves the VA, alleviates DME, and may decrease the required number of anti-VEGF injections.